Peran Media Sosial Instagram dalam Memperluas Jangkauan Pasar UMKM Komoditas Kopi Dusun Sirap Kabupaten Semarang - Sutanto, Himawan Arif; Waluyo, Yanuar Rachmasnsyah J.; Styowati, Widhy; Safitri, Nova Dwiasti; Tanjung, Dewi Sekar (EconBank: Journal of Economics and Banking, 2024)
Social media, especially Instagram, has become an effective marketing tool for micro, small, and medium enterprises (MSMEs) to reach a wider market. This study aims to identify the role of Instagram in expanding the market reach of coffee commodity MSMEs in Dusun Sirap, Semarang Regency. With a qualitative approach, this study involved in-depth interviews with MSME actors, analysis of Instagram upload content, and literature studies. The results of the study show that Instagram plays a significant role in increasing product visibility, building interactions with consumers, and creating brand loyalty. The strategy of using Instagram features such as Reels, Stories, and Instagram Ads also makes a major contribution to expanding market reach.